Media Pembelajaran Alat Transportasi Untuk AnakBerdasar Construct 2 - Haryono, Ganjar Arasy; Umi Fadlilah, S.T., M.Eng (2016)
Transport is facility to the displacement man or goods from place to place by using a vehicles driven by man or machine. Transport used to ease human in doing activity daily. Transportation itself have been divided into three types of, ground transportation, the sea, and air. It is better if we know kind of a means of transportation early, therefore need of media to help children recognize kind of a means of transportation. One through game in a computer by giving stuff on transportation and give viewing pictures 2 dimensions of the kind of transportation. The computer can be used as one of the media learning effective and interactive, which functions to ease for learning to the matter. In order to make the children will be easier understanding and not bored when studies of the type of a means of transportation. Designed up learning made using game engine construct 2 based html 5 with processors use the feature visual effect and setting event and action on each layout. In the application of this game layout first will be displayed menu learn where will appear description of a means of transportation land, the sea, and air, and will appear sound to assist with the learning. Then on the menu game was asked to match parts of the separate transport. The methodology done with an early stage gathering information, after complete data continued with design application system needs corresponding analysis as a reference in making applications, the next process is making of the application to in accordance with design design. The next stage of testing of application, what the display application and the application that have been made. Based on tests carried out in kindergarten Songgolangit, Gentan, Sukoharjo can be concluded that 100 % teachers thought that learning by gaming will make child be eager to learn. While, 90 % students argue that the game made was incredibly exciting to play.